Gender, Class and Food - M. Parsons, Julie. author. aut Link
VIII, 195 p.
Keywords: Everyday foodways are a powerful means of drawing boundaries between social groups and defining who we are and where we belong. This book draws upon auto/biographical food narratives and emphasises the power of everyday foodways in maintaining and reinforcing social divisions along the lines of gender and class.